Detection of beta-lactamase production in clinical Prevotella species by MALDI-TOF MS method. (October 2020) - Toprak, Nurver Ulger; Akgul, Oncu; Sóki, József; Soyletir, Guner; Nagy, Elisabeth; ,; Leitner, Eva; Wybo, Ingrid; Tripkovic, Vesna; Justesen, Ulrik S.; Jean-Pierre, Helene; Stingu, Suzana C.; et al.
Abstract: Penicillins, can be used in treatment of infections due to Prevotella species if they are susceptible to penicillin. Early and accurate preliminary detection of β-lactamase-producing isolates is crucial for treatment of infection. The aim of this study was to determine β-lactamase-producing Prevotella species by MALDI-TOF MS and screen them for the presence of cfx A gene, responsible for β-lactamase production. A total of 500 clinically relevant Prevotella isolates, collected from 13 countries for the previous European antibiotic resistance surveillance study, were tested. Susceptibility testing was performed against ampicillin and ampicillin/sulbactam by Etest methodology. EUCAST guidelines were used for susceptibility interpretations; the isolates with MIC value ≤ 0.5 for ampicillin were considered susceptible and >2 resistant. All Prevotella isolates, were tested for detection of β-lactamase activity by MALDI-TOF MS (Vitek® MS Research Use Only) system and the presence of the cfx A gene by PCR method. The susceptibility levels of the isolates to ampicillin/sulbactam and ampicillin were 99.6% and 43.4%, respectively. A total 59% of isolates presented β-lactamase activity and 60.8% were cfx A gene positive. Both these tests were positive for isolates in the resistant category. Additionally, >95% of the isolates (n = 65) which ampicillin MIC values ranged from >0.5 μg/mL to 2 μg/ml displayed β-lactamase activity. We also found that the MALDI-TOF MS-based β-lactamase assay delivers results in 2 h. We found a high concordance between the MALDI-TOF MS β-lactamase results in terms of cfx A β-lactamase gene presence. MALDI-TOF MS may serve as a simple and efficient alternative method of the existing phenotypic and PCR-based methods. Highlights: 500 Prevotella isolates were tested for β-lactamase activity by MALDI-TOF MS. Ampicillin hydrolysis assay detected β-lactamase production in resistant isolates. More than 95% of isolates in the category "I" displayed β-lactamase activity. MALDI-TOF MS β-lactamase results and presence of cfx A gene showed high correlation. MALDI-TOF MS may be an efficient alternative to phenotypic and PCR-based methods.